Supercapacitors Based on Activated Carbon and Polymer Electrolyte (International Journal of Sustainable Energy and Environmental Research, 2012)
The supercapacitors are characterized by fast discharge rate and easy for maintenance. Their demand is predicted to be most extensive in frequency regulation applications. The other area for significant growth is in regenerative braking for grid–connected light rail systems. In this research we fabricated a Supercapacitor using a commercially prepared Activated carbon which was sized to an area of 1 cm2 and combinations of two electrolytes solutions; polymer electrolyte polyvinyl alcohol (PVA) and Phosphoric acid (H3PO4) assembled in an innovative supercacitor tester. The result indicates a relatively high efficiency of about 90 % and also exhibited long cyclability of life time under different voltage windows.